The strength of weak national ties: The economic sociology of nation-building - Dan Lainer-Vos (economic sociology. perspectives and conversations, 2022)
In 1949, months after the conclusion of the Israeli war of independence, Arthur Hertzberg, a devoted young Zionist who later became a renowned historian, decided to witness with his own eyes the wonders that were taking place in Israel. He traveled across the ocean, but to his surprise, his hosts assailed him with a barrage of demanding questions instead of offering a warm welcome.
Keywords: 300